The Effect of Given Atung Seed Extraction as a Natural Preservative to Changes The Quality Value of Swordfish Smoking - Sandra Hiariey; Vanessa Lekahena (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Atung (Parinarium glaberimmum Hassk) was tropical plant as potential as antimicrobial muchgrown in Eastern Indonesia especially in Maluccas area. The aim of this research was to determinethe chemical characteristics of smoked swordfish was soak in extract atung seed before smoking.Measurement parameter of chemical characteristics covering the moisture conten, levels of ash,levels of fat, levels of a protein micro method Kjeldahl ash (AOAC 2005), carbohydrates (methodby difference) and microbiologi. The observation is made every day storage 2 days up 4 days. Thisresearch used Factorial Randomized Design with 3 replication. Data analysis statistic univariateusing software SPSS 20. The results of this research show the swordfish were soak in extract atungseed before smoking affect the chemical characteristics and microbiologi. Swordfish smokedwith extract atung seed and room tempareture storage were given significant effect (α=5%) to themicrobes total. The best value of swordfish in soak of atung extract at first production with valueof microbes 2,6x104 CFU. The chemical characteristics analysis result show differences amongthe treatments during the storage room temperature. The best values of chemical characteristicsswordfish smoked at 2 days room temperature storage with moisture level 59,46%, ash level 2,66%,fat level 1,63%, protein level 34,62% and carbohydrat level 1,63%.Keywords : Atung seed, natural preservative, quality